PENINGKATAN KEMAMPUAN KOMUNIKASI DAN KEMAMPUAN KONEKSI MATEMATIS SISWA MELALUI PENDEKATAN KONTEKSTUAL DI SMP - Imas Sabtiyah Khoadah; Devi Erliana Sari; Luvy Sylviana Zanthy (Journal on Education, 2019)
The purpose of this study was to explain the improvement in communication skills and mathematical connections of students after being given a contestant learning approach. The research was carried out experimentally at Budi Bakti Utama Middle School. The experimental class gets learning with a contextual approach while the control class gets conventional learning. The instrument consists of tests of learning devices to measure students' communication skills and mathematical connections. The test is done twice with the same questions, namely before and after learning (pretest-posttest). The research hypothesis was tested using the average difference test, namely the t-test. The results of the study showed: (1) Increased mathematical communication skills of the experimental class students more than the mathematical communication skills of the control class, and (2) Increasing the mathematical connection ability of the experimental class students more than the mathematical connection ability of the control class.